Discourses, Practices and Performances in Sámi Museology at Tromsø University Museum - Ragazzi, Rossella; Nerici, Giacomo (Nordisk Museologi, 2020)
This article focuses on the set up, reception, and social scientific discursive fields that have informed two exhibitions about Sami culture curated over time by Tromsø University Museum. They were curated in two different periods in the recent history of the Sami (end of 1990s and 2013-15). In our anthropologically-informed analysis we take a second look at the way in which researchers and curators have constructed, performed, and narrated certain aspects of Sámi material and immaterial heritage, in times of change and political awareness. The recent exhibitions have contributed to articulate essential issues concerning ethnic identity and cultural belonging in conversation with or critique towards the previous representation of Sámi ethnography at the museum, especially the renown "Sámekulturen" curated by professor Ørnulf Vorren. How did these exhibitions handle the representations in which Sámi people would mirror their history, identity and aesthetics? How did they speak on behalf of the Sámi but also in conversation with the Sámi? How were these presentations interpreted over time in a changing museological practice?